2023
DOI: 10.1111/1753-0407.13346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile health interventions on health‐related outcomes in older adults with type 2 diabetes: A systematic review and meta‐analysis

Abstract: Background Type 2 diabetes mellitus (T2DM) is a chronic metabolic condition that is associated with multiple comorbidities. Apart from pharmacological approaches, patient self‐management remains the gold standard of care for diabetes. Improving patients' self‐management among the elderly with mobile health (mHealth) interventions is critical, especially in times of the COVID‐19 pandemic. However, the extent of mHealth efficacy in managing T2DM in the older population remains unknown. Hence, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
5
1
1
Order By: Relevance
“…It is crucial that healthcare professionals become guides in the use of technologies as new methods of learning. It has been reported that this approach increases patient trust, a better adherence to treatment and motivation in health education can be achieved (29,30). When the patients become acquainted with an education web site it is necessary and very important the follow-up by healthcare professionals.…”
Section: Mean and Standard Deviationmentioning
confidence: 99%
“…It is crucial that healthcare professionals become guides in the use of technologies as new methods of learning. It has been reported that this approach increases patient trust, a better adherence to treatment and motivation in health education can be achieved (29,30). When the patients become acquainted with an education web site it is necessary and very important the follow-up by healthcare professionals.…”
Section: Mean and Standard Deviationmentioning
confidence: 99%
“…Recientes estudios en China demuestran que el efecto benéfico del uso de cardiometabolitos como los glicosilados de hemoglobina en pacientes adultos mayores con Diabetes Mellitus Tipo 2, (20).…”
Section: Artículo Originalunclassified
“…Digital health technologies, such as smartphone-based mobile apps or wearables, allow the measurement and tracking of clinical parameters, such as pain, fatigue, fever, arrhythmias, slower walking speed, and insufficient physical activity to prevent or improve the management of chronic diseases, frailty, morbidity, and mortality [ 7 ]. For instance, in older adults with type 2 diabetes mellitus, digital health interventions (ie, mHealth) have been shown to be effective in improving cardiometabolic outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%